Reflective practice and the development of competencies for health promotion in nurses’ training - Netto,Luciana (2018)
ABSTRACT Objective: To analyze the insertion in reflective professional practice as a strategy for the development of competencies for health promotion in nurses’ training. Method: Case study, qualitative approach anchored in the theoretical-methodological framework of the Marxist dialectic. Data were obtained from documents, interviews with graduated students and focus groups with teachers from a nursing higher education institution located in the state of Minas Gerais, Brazil. Data were examined by critical discourse analysis. Results: The most favorable contexts to reflective practice in the development of competencies for health promotion involve the practice of teaching-service-community integration, teacher-student interaction and teamwork. The discourse of early insertion is hegemonically constructed as a social practice of the study scenario. Conclusion: The characteristics of the curricular proposal of the study scenario favor the ‘learning to do’ mediated by experience and reflexivity by mobilizing the development of competencies for health promotion. In addition to insertion, students’ immersion in the reality of services generates experiences in a reflective-critical process.